THE MODERATING ROLE OF ESG ON THE RELATIONSHIP BETWEEN GRI COMPLIANCE AND CORPORATE VALUE(THE MODERATING ROLE OF ESG IN THE RELATIONSHIP BETWEEN GRI COMPLIANCE AND FIRM VALUE) - Ditha Ayu Pratama; Dwi Hartanti (RADJA PUBLIKA, 2025)
Sustainability issues have encouraged companies to increase transparency through Global Reporting Initiative (GRI)-based reporting. However, the existence of sustainability reports does not necessarily reflect real sustainability practices. This study aims to examine the effect of GRI Compliance on firm value and evaluate the role of Environmental, Social, and Governance (ESG) Score as a moderating variable. This study uses a quantitative approach with secondary data from 224 non-financial companies listed on the Indonesia Stock Exchange and Bursa Malaysia during the period 2021–2023. Multiple linear regression models with moderation analysis are used to test the relationship between variables. The results show that GRI Compliance has a positive effect on firm value in both countries. However, ESG Score only acts as a significant moderator in Malaysia, while in Indonesia its role is not significant. This finding indicates that the effectiveness of ESG Score as a sustainability signal booster is greatly influenced by the level of regulatory development and market understanding of sustainability. Thus, companies in developing countries need to not only improve the quality of sustainability reporting but also strengthen ESG implementation to gain market recognition. This study provides important implications for regulators and business actors in designing sustainability reporting policies and strategies that are more accountable and have an impact on firm value. This research also strengthens the urgency of adopting ESG Score as a credible external assessment tool.